Source current type active filter N-dimention matrix application in AC drives - Gulez, K; Pastaci, H; Uzunoglu, M; Mutoh, N (IEEE, 2003)
The source current detection type AF (Active Filter) has a merit of robustness to the load variation, but a problem of the resonance between the AF and an LC filter often arises, if an LC filter is connected parallel to the AF. In this paper, Triple-LISN (Line Impedance Stabilization Network) circuit based AF, resonance analysis and the simulation results comparing with experimental ones are studied and discussed. According to the type of the application and the effect of noise and harmonic problem, the suitable number of AF can easily be selected with small changes on the n-dimension matrix topology for all AC Drives.
Keywords: source current type active filter; noise suppression; ac drives; control systems and harmonic reduction; Automation & Control Systems; Computer Science; Instruments & Instrumentation; Remote Sensing; Imaging Science & Photographic Technology